Development of Agritourism Program of Pattana Maipon Permpoonsap Community Enterprise, Surat Thani Province - Marchoo, Witchuta; Jaikrajang, Buntarika; Thitithanakul, Suraphon (Area Based Development Research Journal, 2022)
Despite being well-known for the agriculture of Rongrien rambutan, Pattana Maipon Permpoonsap community enterprise, Ban Nasan district, Surat Thani province still lacked tourism promotion activities. Thus, this paper aimed to develop an agritourism program to add value to large rambutan orchards under Pattana Maipon Permpoonsap community enterprise, A Participatory Action Research (PAR) was designed and employed for the development process which involved the following steps: 1) the enterprise members jointly determined their needs in the development, 2) a survey on the potential of the members’ orchards and a design of a tour program was conducted, 3) an agri-tourism program testing along with cost and pricing calculations were conducted, and 4) a reflection and a workshop on service and tourism interpretation skills were delivered. As a result, Pattana Maipon Permpoonsap community enterprise had two agricultural tour programs highlighting rambutan orchards certified by GAP standards, and the sole GI-certified rambutan in Thailand for its famous crispy texture and sweetness. Moreover, the community enterprise collaborated with local restaurants to promote local menus and located near other well-known agricultural attractions of Ban Nasan district, such as Suan Sala Arthit, and natural attractions in Surat Thani and nearby provinces. Finally, the community enterprise also worked with Wangkho resort to promote and offer the programs to visitors.